Toxoplasma gondii Mechanisms of Entry Into Host Cells - Portes, Juliana; Barrias, Emile; Travassos, Renata; Attias, Márcia; de Souza, Wanderley (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii, the toxoplasmosis agent, is an obligate protozoan parasite able to infect a wide range of homeothermic vertebrate cells. Its internalization involves an initial recognition of the host cell surface followed by the secretion of proteins from secretory organelles, such as micronemes and rhoptries, that assemble a macromolecular complex and form a specialized structure designated as a “moving junction”. The parasite is then internalized via an endocytic process with the formation of a parasitophorous vacuole, where the parasites survive and multiply. Using different cell types and inhibitors of distinct endocytic processes, we show that treatment of host cells with compounds that interfere with clathrin-mediated endocytosis (hypertonic sucrose medium, chlorpromazine hydrochloride and pitstop 2) significantly inhibited the internalization of tachyzoites. In addition, treatments that interfere with macropinocytosis, such as incubation with amiloride or IPA-3, increased parasite attachment to the host cell surface but significantly blocked parasite internalization. Immunofluorescence microscopy results showed that markers of macropinocytosis, such as the Rab5 effector rabankyrin 5 and Pak1, are localized in parasite-containing cytoplasmic vacuoles. These results indicate that entrance of T. gondii into mammalian cells involves both well characterized parasite machinery and host cells endocytic machinery such as the clathrin-mediated endocytic process, and macropinocytosis.